CD34+ selected peripheral blood Stem Cell Boost (SCB) for Poor Graft Function (PGF) or mixed chimerism in pediatric patients, after hematopoietic stem cell transplantation: Results of a retrospective multicenter study. (3rd November 2020) - Berger, Massimo; Faraci, Maura; Saglio, Francesco; Giardino, Stefano; Ernestina Vassallo, Elena; Prete, Arcangelo; Fagioli, Franca
Abstract: Background: PGF is historically associated with high morbidity and mortality after allogeneic hematopoietic stem cell transplantation (allo‐HSCT). Methods: In this study, we report our multicenter experience on stem cell boost (SCB) for PGF, or incomplete donor engraftment, in 16 pediatric patients. Donors were HLA‐matched siblings (n = 4), unrelated donors (n = 11), or haploidentical family members (n = 1). Ten patients had two‐lineage cytopenia, 5 had one‐lineage cytopenia, and 1 had poor immunological reconstitution together with a low percentage of donor cell engraftment. A median of 6.6x10 6 selected CD34+/Kg was infused after 194 days from allo‐HSCT (48‐607). Results: In 4 out of 5 patients, one‐lineage cytopenia was resolved, while among the 10 patients with two‐lineage cytopenia, 4 resolved both cytopenia, 5 resolved one‐lineage, and one did not respond. All patients reverted their mixed chimera to full donor chimera. OS was 56%, transplant‐related mortality (TRM) 32%, and RI 12%. The main causes of failure were related to infections with 4 out of 7 deaths caused by this. Conclusions: SCB may rescue over 50% of patients with PGF after allo‐HSCT. An earlier treatment may reduce the infectious complications and improve survival.